2018
DOI: 10.1080/10903127.2018.1525458
|View full text |Cite
|
Sign up to set email alerts
|

Need to Prioritize Education of the Public Regarding Stroke Symptoms and Faster Activation of the 9-1-1 System: Findings from the Florida–Puerto Rico CReSD Stroke Registry

Abstract: Objective: Demographic differences (race/ethnicity/sex) in 9-1-1 emergency medical services (EMS) access and utilization have been reported for various time-dependent critical illnesses along with associated outcome disparities. However, data are lacking with respect to measuring the various components of time taken to reach definitive care facilities following the onset of acute stroke symptoms (i.e., stroke onset to 9-1-1 call, EMS response, time on-scene, transport interval) and particularly with respect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…After screening studies based on titles and abstracts, 56 studies were excluded. The full articles of the remaining 32 studies were reviewed, and 30 studies were included in the quantitative synthesis 14,20–48 (see the Figure for PRISMA chart [Preferred Reporting Items for Systematic Reviews and Meta-Analyses]). The characteristics and racial makeup of each included study are presented in Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After screening studies based on titles and abstracts, 56 studies were excluded. The full articles of the remaining 32 studies were reviewed, and 30 studies were included in the quantitative synthesis 14,20–48 (see the Figure for PRISMA chart [Preferred Reporting Items for Systematic Reviews and Meta-Analyses]). The characteristics and racial makeup of each included study are presented in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, 1 study reported shorter time to treatment for Hispanic and Black patients as compared with non-Hispanic White patients. 42 One study reported similar times to treatment for Hispanic patients when compared with White patients. 21 When dichotomized, arrival rates to the health care facility within 3 hours of symptom onset are more common in White patients as compared with African American and Hispanic patients (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After a decade from approval of thrombolysis for stroke treatment, only a modest decrease in pre-hospital delays of 6% per year was noted in an international study 18 . More recent reports from the State of Florida in the US have shown a persistent average delay of 301 min from symptom onset to 911 call 19 . This underlies the importance of more extensive public education on early recognition of stroke symptoms and the urgency of reaching the correct facility for appropriate acute intervention.…”
mentioning
confidence: 98%